COLLECTIONS OF THE WORLD’S CROP GENETIC RESOURCES FOR THE DEVELOPMENT OF PRIORITY PLANT BREEDING TRENDS - K. G. Barylnik (Труды по прикладной ботанике, генетике и селекции, 2018)
Baking properties of flour made from triticale grain were studied employing the improved triticale lines L-30 and MH Alamo bred at the Leningrad Research Institute of Agriculture "Belogorka" and the cultivars ‘Quasar’ and ‘Mamuchar’ with a predominance of rye and wheat genotypes developed at the North Caucasian Federal Agricultural Research Center. Grain, flour of single-grade grinding, and test baking products were compared using two methods. Laboratory baking was carried out according to the standard method GOST 27669-88 for wheat flour and by the method of St. Petersburg Branch of the Baking Industry Research Institute with the leaven developed for rye flour. The method of test baking with leaven is preferred for evaluation of triticale with weak gluten.